Pengaruh antara Kecemasan dan Fasilitas Belajar Terhadap Prestasi Belajar Siswa di SMA Negeri 3 Ambon - Beatrix Salenussa; Leonardo Stevy Pariama; Nova M. Mataheru (Jurnal Ilmiah Wahana Pendidikan, 2019)
This study aims to determine the effect of anxiety and learning facilities with student learning achievement in Ambon 3 senior high school. The research method used is a quantitative method with the research subject being eleventh grade students. Data collection using anxiety instruments modified from the Beck Anxiety Inventory and learning facility instruments using the School Facility Survey, while data on student achievement were taken from the documentation of students' pure grades. Data processing was measured using correlation analysis Product Moment with the help of the program SPSS. The results of his research indicate that there is a significant joint effect between anxiety and learning facilities with student achievement in high school 3 Ambon with a correlation coefficient rx1.2y = 0.228, p = 0.015 <0.05. This concludes that anxiety and learning facilities together are very influential on student achievement in high school 3 Ambon.